Reduction of invertebrate herbivory by land use is only partly explained by changes in plant and insect characteristics. Issue 2 (22nd March 2023) - Neff, Felix; Prati, Daniel; Achury, Rafael; Ambarlı, Didem; Bolliger, Ralph; Brändle, Martin; Freitag, Martin; Hölzel, Norbert; Kleinebecker, Till; Knecht, Arturo; Schäfer, Deborah; Schall, Peter; et al.
Abstract: Invertebrate herbivory is a crucial process contributing to the cycling of nutrients and energy in terrestrial ecosystems. While the function of herbivory can decrease with land‐use intensification, the underlying mechanisms remain unclear. We hypothesize that land‐use intensification impacts invertebrate leaf herbivory rates mainly through changes in characteristics of plants and insect herbivores. We investigated herbivory rates (i.e., damaged leaf area) on the most abundant plant species in forests and grasslands and along land‐use intensity gradients on 297 plots in three regions of Germany. To evaluate the contribution of shifts in plant community composition, we quantified herbivory rates at plant species level and aggregated at plant community level. We analyzed pathways linking land‐use intensity, plant and insect herbivore characteristics, and herbivory rates. Herbivory rates at plant species and community level decreased with increasing land‐use intensity in forests and grasslands. Path analysis revealed strong direct links between land‐use intensity and herbivory rates. Particularly at the plant community level, differences in plant and herbivore composition also contributed to changes in herbivory rates along land‐use intensity gradients. In forests, high land‐use intensity was characterized by a larger proportion of coniferous trees, which was linked to reduced herbivory rates. In grasslands, changes in the proportion of grasses, plant fiber content, as well as the taxonomic composition of herbivore assemblages contributed to reduced herbivory rates. Our study highlights the potential of land‐use intensification to impair ecosystem functioning across ecosystems via shifts in plant and herbivore characteristics. De‐intensifying land use in grasslands and reducing the share of coniferous trees in temperate forests can help to restore ecosystem functionality in these systems.